Advances in Biomaterials for Drug Delivery. Issue 29 (7th May 2018) - Fenton, Owen S.; Olafson, Katy N.; Pillai, Padmini S.; Mitchell, Michael J.; Langer, Robert
Abstract: Advances in biomaterials for drug delivery are enabling significant progress in biology and medicine. Multidisciplinary collaborations between physical scientists, engineers, biologists, and clinicians generate innovative strategies and materials to treat a range of diseases. Specifically, recent advances include major breakthroughs in materials for cancer immunotherapy, autoimmune diseases, and genome editing. Here, strategies for the design and implementation of biomaterials for drug delivery are reviewed. A brief history of the biomaterials field is first established, and then commentary on RNA delivery, responsive materials development, and immunomodulation are provided. Current challenges associated with these areas as well as opportunities to address long‐standing problems in biology and medicine are discussed throughout. Abstract : Biomaterials for drug delivery have enabled the treatment of a wide range of diseases. A historical background is presented alongside recent advances in therapeutic RNA delivery, the engineering of responsive polymers, and immunotherapy strategies against disease. Emerging applications and potential challenges within the biomaterials field are also discussed.